2015
DOI: 10.1155/2015/207534
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Anti-Inflammatory Effects Did Not Improve Organ Quality in Brain-Dead Rats

Abstract: Effect of glucocorticoid administration on improving the outcomes of kidney and liver allografts has not been clearly elucidated. This study investigated the effect of prednisolone administration after onset of brain death (BD) on kidney and liver in a controlled rat model of BD. BD was induced in rats by inflating an epidurally placed balloon catheter. Animals were treated with saline or prednisolone (5, 12.5, or 22.5 mg/kg) one hour after the onset of BD. After 4 hours of BD, experiments were terminated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(45 reference statements)
0
9
0
1
Order By: Relevance
“…ECD livers are vulnerable to hypoxia and tissue injury associated with DGF or graft survival. In order to improve the quality of these suboptimal liver grafts, several studies evaluated the effect of intervention during donor management, such as the administration of steroids, dopamine, and hormone replacement (10, 11, 53). Taken these data into account, the current strategies applied in LiTx have mainly been focusing on treatments to stabilize hemodynamic disorders associated with deceased donation.…”
Section: Liver Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…ECD livers are vulnerable to hypoxia and tissue injury associated with DGF or graft survival. In order to improve the quality of these suboptimal liver grafts, several studies evaluated the effect of intervention during donor management, such as the administration of steroids, dopamine, and hormone replacement (10, 11, 53). Taken these data into account, the current strategies applied in LiTx have mainly been focusing on treatments to stabilize hemodynamic disorders associated with deceased donation.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Again, prednisolone reduced the levels of pro-inflammatory cytokine gene expression, but did not increase nor decrease the C3 expression compared to untreated DBD rats. These divergent C3 expressions after administration prednisolone are not fully understood, but could be explained by the fact that complement is involved in liver regeneration (11).…”
Section: Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in kidney transplantation have revealed that both brain and cardiac death significantly increase C3 expression and complement activation compared with living donors [ 152 , 153 , 154 , 155 ]. Administering steroids prior to transplantation has proved to be an effective anti-inflammatory treatment, although it does not appear to affect increased C3 expression in animal models of deceased donors [ 156 , 157 ]. The role of complement activation following brain death, and targeting complement to reduce transplant injury, have been well reviewed [ 158 ].…”
Section: Role Of Complement In Liver Donation After Brain Verses Cmentioning
confidence: 99%
“…A administração de hormônio tireoidiano, por exemplo, mostra-se capaz de melhorar o estado metabólico e hemodinâmico 65-68 de animais em ME, porém esse resultado não se traduz em melhora clínica de potenciais doadores em uma metanálise 69 . Apesar dos corticoides não demonstrarem benefício em alguns estudos experimentais 70 104 , a ME produz alterações discretas na histologia cardíaca em ratos, que não são modificadas pelo bloqueio epidural. Estudos demostraram que a elevação da troponina-I sérica em potenciais doadores está relacionada ao pior prognóstico do transplante 41,43 .…”
unclassified